2014
DOI: 10.1089/ten.tec.2014.0047
|View full text |Cite
|
Sign up to set email alerts
|

Platform Technologies for Decellularization, Tunic-Specific Cell Seeding, andIn VitroConditioning of Extended Length, Small Diameter Vascular Grafts

Abstract: The aim of this study was to generate extended length, small diameter vascular scaffolds that could serve as potential grafts for treatment of acute ischemia. Biological tissues are considered excellent scaffolds, which exhibit adequate biological, mechanical, and handling properties; however, they tend to degenerate, dilate, and calcify after implantation. We hypothesized that chemically stabilized acellular arteries would be ideal scaffolds for development of vascular grafts for peripheral surgery applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…70,88 The aforementioned advantages of PGG have paved the path for its use in tissue engineering studies of valves, development of vascular grafts, and numerous other potential therapeutic applications. 32,33,35,39,47,88,119,120,129,154,156,167,168,170,171 In this review, we critically evaluate recent work relevant to drug-delivery and translation-related applications of PGG.…”
Section: Functionality Of Pentagalloyl Glucosementioning
confidence: 99%
“…70,88 The aforementioned advantages of PGG have paved the path for its use in tissue engineering studies of valves, development of vascular grafts, and numerous other potential therapeutic applications. 32,33,35,39,47,88,119,120,129,154,156,167,168,170,171 In this review, we critically evaluate recent work relevant to drug-delivery and translation-related applications of PGG.…”
Section: Functionality Of Pentagalloyl Glucosementioning
confidence: 99%
“…18,21,36 While some tissues are readily decellularized by simple immersion, we and others have shown that immersion is not an effective means of cell removal from the aortic wall components of the root 21 and also from extended lengths of small and medium diameter arteries. 37 Therefore, we developed a unique perfusion decellularization setup (PDCell system; Aptus, LLC), which has been used extensively (*50 roots have been decellularized using this system in two research laboratories) and was found to be reproducible and repeatable. The system was purposefully designed so that the aortic root is pressurized, expanded, and allowed to recoil cyclically to ensure flow of fluids through the thickness of the aortic wall.…”
Section: Novel System For Perfusion Decellularizationmentioning
confidence: 99%
“…Importantly, these decellularized tissues show promise for therapeutic tissue regeneration in a variety of applications. [1-7] Development of decellularized native tissues led to the production of tissue-engineered scaffolds which retained basement membrane proteins such as collagen type IV, laminin, and fibronectin that enhance cellular adhesion [8, 9] and invoke signaling to influence cellular differentiation and regenerative potential [10-12]. Growth factors including transforming growth factor-beta, basic fibroblast growth factor (FGF), hepatocyte growth factor and vascular endothelial growth factor (VEGF) persist in their bioactive form within ECM bioscaffolds after sterilization.…”
Section: Introductionmentioning
confidence: 99%